PENGARUH PENERAPAN METODE SURVEY, QUESTION, READ, RECITE AND REVIEW (SQ3R) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIIIA DAN VIIIC SMPN 10 PADANG TAHUN PELAJARAN 2013/2014 - Indriyeni, Teti; Mukhni, Mukhni; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
Based on background knowledge of this research was understanding of mathematical concept still low and their habit was waiting the answer from their friend. This research is to determine whether studentsâ understanding of concept mathematics by using SQ3R methode better than studentsâ understanding of concept mathematics by using conventional strategy at VIIIA and VIIIC SMPN 10 Padang. Type of this research was experiment. Population of this research was students at VIIIA and VIIIC SMPN 10 Padang, and sample of this research was students class VIIIC as experimental class and VIIIA as control class. Post-Test was as instrumentation in this research, with reliability 0.991. From the data analysis get mean score from studentsâ achievement in experimental class was 84.85 that high rather than in control class that was 67.44. Data analysis was done by using hypothesis testing. Tcalculated= 6.03 and ttable= 1.70. Â so hypothesis was acceptable. So, we can conclude that studentsâ understanding of concept mathematics that used Quiz Team methode better than conventional strategy at VIIIA and VIIIC Grade of SMPN 10 Padang.